Analisis Pengaruh Keselamatan dan Kesehatan Kerja (K3) dada Pekerja Parkir di Area Parkir Plaza Kenari Mas - Sudewo (Universitas Pamulang, 2024)
Occupational Safety and Health (K3) is an important aspect in the work environment, especially in the parking sector which has a high risk of accidents. This study aims to analyze the effect of worker awareness and supervision on compliance with K3 standards in the Plaza Kenari Mas parking area. The research method used is a quantitative approach with multiple linear regression analysis and strategy evaluation through SWOT analysis. Data were collected through a survey of 30 parking workers using a purposive sampling technique. The results of the study showed that worker awareness factors have a significant effect on K3 compliance with a regression coefficient of 0.208. Supervision also plays an important role in increasing compliance with a higher regression coefficient, namely 0.324. The results of the statistical test support this finding, where the t-test shows that both awareness and supervision have a significant effect on worker compliance with K3 standards (t count = 2.103 and 2.608 greater than t table). The SWOT analysis identified that the optimal strategy to improve K3 implementation includes regular training, increased supervision, provision of safety facilities, and implementation of incentives and sanctions. Thus, this study concludes that increased worker awareness and tighter supervision from management can improve compliance with OHS standards. The implication of this study is the need for more effective managerial policies in implementing OHS systems, including optimizing training, supervision, and regulation to create a safer and more productive work environment in the parking sector. Keywords: Occupational Safety and Health (OHS), SWOT, Linear Regression.